2020
DOI: 10.1016/j.ejogrb.2020.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Being an obstetrics and gynaecology resident during the COVID-19: Impact of the pandemic on the residency training program

Abstract: Objective to evaluate the impact of the COVID-19 pandemic on the obstetrics and gynecology residency training program in Italy. Study design This was a cross-sectional survey study aimed to assess the impact of the COVID-19 pandemic on the obstetrics and gynecology residency training program in Italy. An online survey with 45 questions was sent and completed anonymously by residents after accepting an informed consent. The invitation to the online survey was sent to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 13 publications
6
60
0
Order By: Relevance
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…Since its outbreak in December 2019, the COVID-19 pandemic has affected health care globally and inadvertently has had a huge impact on residency training programs worldwide [2][3][4]. Through our survey, we endeavoured to focus on the effect of COVID-19 pandemic on teaching and training in Obstetrics and Gynaecology in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of specialties such as surgery and radiology, have shown a significant impact on the training needs of residents during the pandemic [2,3]. A survey conducted on Italian obstetrics and gynaecology (ObGyn) trainees specifically showed a marked disruption of training and changes to the training program [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite OVID Medline having been nominated as the primary database for the search and yielding six sources, more sources were identified in both Web of Science (12) and Scopus (9) databases. Due to the large number of countries (17) from which authors published their studies, sources were categorised by continent of origin. The majority of these were from North America (13, 40.6%) and Europe (12, 37.5%), with the remainder from Asia (3, 9.4%), South America (2, 6.3%) and the Middle East (2, 6.3%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sources scoring higher than the mean (13, 46.4%) tended to have a higher response rate, increased complexity of data analysis or higher-level educational outcomes. [10][11][12][13][14][15][16][17][18][19][20][21][22]…”
Section: Reviewmentioning
confidence: 99%